$2.3 trillion spending bill includes COVID‐19 relief, adding $1.65 billion to SAPT BG. Issue 2 (9th January 2021) - Knopf, Alison
Abstract : Just before Christmas, Congress passed a $2.3 trillion spending package that included $1.4 trillion in appropriations for fiscal year 2021 and $900 billion for COVID‐19 relief (another "stimulus" bill). The appropriations bill level‐funded the Substance Abuse Prevention and Treatment block grant (SAPT BG) at $1.858 billion, and level‐funded the State Opioid Response (SOR) grant at $1.5 billion (this grant program includes stimulants as of last year). However, the COVID‐19 relief part of the law gave the SAPT BG an extra $1.65 billion for FY 2021.